Instrumenty prawne służące zabezpieczeniu społecznemu rodziny - Ziółkowska, Krystyna (Studia Prawnoustrojowe, 2019)
Security of employment nowadays is an important element of the individual’s functioning in the state. When economic development in the country increases – new employment opportunities also appear. Growth in employment is a condition for further economic development. With the economic difficulties of the state, high unemployment and a slowing economy – there are also demographic problems. The issue of benefits available through the Polish social system for full and incomplete families and the legal basis for their granting require clarification. The Constitution of the Republic of Poland puts families under the protection of the state, which should properly implement a family-oriented policy and, above all, protection from a legal point of view. State policy should be aimed at providing the best conditions for starting and expanding families, in order to secure generational replacement and a fair pension system. Legal regulations indicate which rights families can use.